Isolation and selection of cellulolytic bacteria from rice straw for consortium of microbial fuel cell - Nur Syafira Khoirunnisa; SYAIFUL ANWAR; DWI ANDREAS SANTOSA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Khoirunnisa NS, Anwar S, Santosa DA. 2020. Isolation and selection of cellulolytic bacteria from rice straw for consortium of microbial fuel cell. Biodiversitas 21: 1686-1696. Cellulose such as in rice straw can be utilized as an organic substrate in Microbial Fuel Cell (MFC) to generate electricity by microorganisms as a biocatalyst. This research aimed to get cellulose-degrading bacteria with high capability to degrade rice straw and able to be used as consortium with exoelectrogen bacteria in Microbial Fuel Cell. The stages of research included: (i) isolation of the bacteria using carboxymethylcellulose (CMC) agar medium, (ii) selection of the isolates for that purpose, (iii) enzyme assay and MFC performance test, and (iv) identification of selected isolate. There were 125 isolates that were obtained. Selection based on the ability to degrade cellulose as indicated by clear zone on CMC medium resulted in 23 isolates. Ten isolates belong to anaerobic facultative bacteria were selected. Three of them were synergistic with exoelectrogen bacteria. The three isolates were tested for exoglucanase (Avicel) and total enzyme activity (Filter Paper) with the highest results were 6.21 U/mL (isolate J404) and 5.88 U/mL (isolate J401), respectively. The optimum MFC performance was achieved by one isolate, J401, which produced highest voltage of 40.8 mV and a power density of 0.33 mW/m2. The best isolate, J401, was identified as Xanthomonas translucens based on 16S rRNA method.